Characterization and functional analysis of four glutathione S-transferases from the migratory locust, Locusta migratoria - Qin, Guohua; Jia, Miao; Liu, Ting; Zhang, Xueyao; Guo, Yaping; Zhu, Kun Yan; Ma, Enbo; Zhang, Jianzhen (My University, 2013)
Glutathione S-transferases (GSTs) play an important role in detoxification of xenobiotics in both prokaryotic and eukaryotic cells. In this study, four GSTs (LmGSTd1, LmGSTs5, LmGSTt1, and LmGSTu1) representing different classes were identified from the migratory locust, Locusta migratoria. These four proteins were heterologously expressed in Escherichia coli as soluble fusion proteins, purified by Ni[superscript 2+]-nitrilotriacetic acid agarose column and biochemically characterized. LmGSTd1, LmGSTs5, and LmGSTu1 showed high activities with 1-chloro-2, 4-dinitrobenzene (CDNB), detectable activity with p-nitro-benzyl chloride (p-NBC) and 1, 2-dichloro-4-nitrobenzene (DCNB), whereas LmGSTt1 showed high activity with p-NBC and detectable activity with CDNB. The optimal pH of the locust GSTs ranged between 7.0 to 9.0. Ethacrynic acid and reactive blue effectively inhibited all four GSTs. LmGSTs5 was most sensitive to heavy metals (Cu[superscript 2+] and Cd[superscript 2+]). The maximum expression of the four GSTs was observed in Malpighian tubules and fat bodies as evaluated by western blot. The nymph mortalities after carbaryl treatment increased by 28 and 12% after LmGSTs5 and LmGSTu1 were silenced, respectively. The nymph mortalities after malathion and chlorpyrifos treatments increased by 26 and 18% after LmGSTs5 and LmGSTu1 were silenced, respectively. These results suggest that sigma GSTs in L. migratoria play a significant role in carbaryl detoxification, whereas some of other GSTs may also involve in the detoxification of carbaryl and chlorpyrifos.
Keywords: Glutathione S-transferases; Migratory Locust; Locusta migratoria